(untitled) (Fiep Bulletin - online, 2017)
This study aimed to present an institutional proposal, aimed at improvement of spaces in the context of a university in the state of Rio Grande do Sul had the following objectives:. Check some structural situations for better accessibility of serviced, identify, point and suggest possible solutions to include, in addition to check if the context meets the norms of accessibility. The data and images were authorized by the institution, taking into account the ethical aspects and the Ethics and Research Committee. Based on the data collected and evaluated, we observed that, despite having some elements in your physical space that fit the accessibility standards presented in NBRS, but some spaces are faulty. Thus, the adjustments suggested in the article come to meet with the mission of the institution, which is the search for an excellent education through innovation, inclusion and community development.